INFLUENCE OF FOOD AVAILABILITY ON THE NUTRITIONAL STATUS OF CHILDREN OF 6 MONTHS TO 23 MONTHS - Manyore, Melvin Salvatore (International Journal of Health Sciences, 2021)
Purpose: The study, therefore, seeks to establish the relationship between the food availability and nutritional status of children of 6 months to 23 months. Specifically, the study will seek to determine the influence of food availability, food accessibility, food utilization and food safety on the nutritional status of children of 6 months to 23 months in Kenya. Methodology: The study will take a case study of Kenyan referral level 5 hospital. The hospital has approximately 600 mothers to children of 6 months to 23 months attending clinic in a month. This study will adopt descriptive cross sectional survey design. The study will target the mothers to the children of 6 months to 23 months. The study will also target the head nurses and Paediatricians from the nursing units in the hospital as the key informants. Stratified random sampling method will be used to select the respondents. That is, from the mothers of children of age groups 6-8 months, 9-11 months and 12-23 months. Data will be collected using self-administered structured questionnaires and the Key informant interview guides (KIIs). The study will use Fisher formula to select a sample size of 201 mothers from the total population. Pre-testing of the instruments will be conducted to determine the validity and reliability of the instrument. Data will be analysed using Statistical Package for Social Sciences (SPSS) version 20. Data will be analyzed using chi-square to test the association between the variables. Binary logistic regression (Odds ratio regression) will be used to test the multivariate relationships between various independent and dependent variables. Findings: The study finds that there is a significant impact of food availability on nutritional status of children of 6 months to 23 months. Unique contribution to theory, policy, and practice: TThe inadequacy and unavailability of healthy and nutritious food in many households especially in the Sub-Saharan Africa indicates the serious level of food insecurity. Hartman, et al. (2016) additionally, finds out that dietary intake is not different by disease status (remission or relapse) however, in the absence of nutritional supplements, food intake is inadequate for many nutrients in many children stomach problems.